The Contribution of The Leg’s Power, Body Balance, and Leg Muscle Flexibility to Front Kick Speed of Young Men Fighter, Tapak Suci Hermitage Banjarnegara Regency - Ansori, Ikhsan; Sulaiman, Sulaiman; Rumini, Rumini (Journal of Physical Education and Sports, 2019)
The Purpose: (1) To find out and analyze the significant relationship between leg strength to the speed of the front kick. (2) To find out and analyze a significant relationship between the balance of the body against the speed of the front kick. (3) To find out and analyze the significant relationship between limb muscles flexibility to the speed of front kick. This research method is a triple correlation. Variables are divided into two namely independent variables: leg strength, body balance, and flexibility of leg muscles. While the dependent variable is the speed of Pencak Silat front kick. Population: A number of 72 male fighters from Tapak Suci in Banjarnegara Regency. The data collection technique uses tests and measurements, namely the standing board jump, dynamic balance, split front, and front kick speed test. Data analysis using multiple regression. Result: (1) There is a contribution of leg strength to the speed of the front kick in pencak silat martial arts. Proven from the results of the analysis obtained a contribution of 40.53%, (2) There is a contribution to the balance of the speed of the front kick in pencak silat martial arts. Proven from the results of the analysis obtained a value of the contribution of 50.74%, (3) There is a contribution of flexibility in the limb muscles to the speed of the front kick in pencak silat. This is proven from the results of the analysis obtained value of the contribution of 8.72%, (4) There is a contribution of leg strength, balance, and flexibility of leg muscles with the speed of front kick in pencak silat martial arts. Proven from the results of the analysis obtained the value of the contribution of 40.31%.